2020
DOI: 10.3390/s20113183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Deep Neural Networks for Semantic Segmentation of Prostate in T2W MRI

Abstract: In this paper, we present an evaluation of four encoder–decoder CNNs in the segmentation of the prostate gland in T2W magnetic resonance imaging (MRI) image. The four selected CNNs are FCN, SegNet, U-Net, and DeepLabV3+, which was originally proposed for the segmentation of road scene, biomedical, and natural images. Segmentation of prostate in T2W MRI images is an important step in the automatic diagnosis of prostate cancer to enable better lesion detection and staging of prostate cancer. Therefore, many rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 52 publications
0
62
0
Order By: Relevance
“…They used a DenseNet-like U-Net for training and achieved a DSC of 89.5% ± 2% in the central gland region and 78.1% ± 2.5% in the PZ. Khan et al [16] used a model resembling the encoder-decoder architecture and only T2W images of two prostate MRI datasets for segmentation and training. They achieved a DSC of 90.8 ± 1.2% in the central gland region and 76.0 ± 3.9% in the PZ by using SegNet [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They used a DenseNet-like U-Net for training and achieved a DSC of 89.5% ± 2% in the central gland region and 78.1% ± 2.5% in the PZ. Khan et al [16] used a model resembling the encoder-decoder architecture and only T2W images of two prostate MRI datasets for segmentation and training. They achieved a DSC of 90.8 ± 1.2% in the central gland region and 76.0 ± 3.9% in the PZ by using SegNet [16].…”
Section: Discussionmentioning
confidence: 99%
“…They allow for the automatic extraction of features and learning from large amounts of data for quantification. The DCNN architecture has been used for prostate segmentation or PCa detection [11,[14][15][16]. In most of these studies, conventional DCNNs were used for semantic image segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [ 25 ] applied class-weighting approach to reduce class imbalance, thus yielding slightly higher DSC for classical UNet and SegNet, though they trained their networks with different number of subjects ( Table 5 ). Dense-2 UNet [ 26 ] produced similar performance as the cascaded 2D UNet [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer (PCa) is the most frequently diagnosed cancer with the second highest mortality in men worldwide in 2018 [ 1 ]. Commonly employed PCa screening methods such as the prostate-specific antigen test are subjective and inaccurate, leading to unnecessary invasive prostate biopsy or misdiagnosis of patients with aggressive PCa [ 2 , 25 ]. Multiparametric magnetic resonance imaging (mpMRI) is noninvasive and together with the Prostate Imaging-Reporting and Data System (PI-RADS) assessment guidelines (PI-RADS v2) allows for better diagnosis, localization, risk stratification, and staging of PCa [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning models (e.g., CNNs) form a specific approach that is directly applied on images to extract, select features, and predict the class (classification) or a value (regression) in an automated fashion. Examples in the PCa literature have observed that this deep learning approach detects malignant lesions [ 125 ], predicts the GS [ 126 ], and segments the ROI [ 127 , 128 ].…”
Section: Radiomics Pipeline For Predicting Tumor Gradementioning
confidence: 99%